The Outcomes of Maternal Immune Activation Induced with the Viral Mimetic Poly I:C on Microglia in Exposed Rodent Offspring - Loewen, Sophia M. (2023)
Maternal immune activation (MIA) can result from a variety of maternal inflammatory factors, including metabolic disorders, nutritional deficits, infections, and psychosocial stress. MIA has been consistently recognized as a major risk factor for neurodevelopmental disorders, and this association seems to be especially important for viral infections as viral exposure during pregnancy was associated with a higher risk of developing neurodevelopmental disorders, such as schizophrenia. In MIA, the gestational parent's inflammatory response to an immune stimulus alters or interrupts fetal development, triggering neurodevelopmental consequences. As MIA can occur in any pregnancy, it is important to understand the many factors at play that contribute to altered brain development in the offspring, especially considering recent global events such as the COVID-19 pandemic. The underlying mechanisms by which MIA results in deleterious outcomes are not yet clear, but due to the inflammatory response it initiates, it is becoming apparent that microglia are critically involved. Through investigation of MIA animal models, the role of microglia in this field is becoming more evident. Compelling evidence from animal models indicates that MIA can disrupt synaptic pruning, neuronal progenitor cell proliferation/differentiation, oligodendrogenesis, and more. Microglia appear as an active player, assisting these neural-related functions during healthy development but also mediating MIA-induced disturbances in these critical processes when neurodevelopment is challenged. The present review illustrates this complex web by reviewing recent literature, focusing on the outcomes of MIA resulting from viral mimetic polyinosinic-polycytidylic acid in rodents, to provide a clear description of how MIA impacts microglial functions and what this means for the offspring's neurodevelopment. Moreover, we discuss the possible implications of the COVID-19 pandemic on the neurodevelopment of the current and next generations in the frame of MIA models and propose some putative pharmacological and non-pharmacological approaches to prevent or attenuate MIA consequences.